Analisis Pengaruh Penempatan dan Pelatihan Pegawai Terhadap Produktivitas Kerja Pada Kantor Kelurahan Jatimulya, Kecamatan Tambun Selatan, Kabupaten Bekasi, Jawa Barat - Akhmad Imron Rosyadi; Budi Rachmawati (Mulia Pratama, 2023)
The purpose of this research is to find out whether the placement of employees and employee training affect work productivity. The research was conducted on all employees so that this research was included in population research. Hypothesis testing uses multiple linear regression analysis, F test and t test, to determine simultaneously and partially the effect of the independent variables on the dependent variable at the 95% confidence level (? = 0.05). The results of the research based on the F test or simultaneously, employee placement and employee training have a positive/significant influence on work productivity at the Jatimulya village office. The result of multiple linear regression analysis is Y = 9.047 + 0.583 X1 + 0.250 X2. Shows that the placement of employees has a greater influence than employee training in increasing work productivity.. We also provide suggestions and implications of the research.